Studying of cellular interaction of hairpin‐like peptide EcAMP1 from barnyard grass (Echinochloa crusgalli L.) seeds with plant pathogenic fungus Fusarium solani using microscopy techniques. Issue 6 (8th February 2016) - Vasilchenko, Alexey S.; Yuryev, Mikhail; Ryazantsev, Dmitry Yu; Zavriev, Sergey K.; Feofanov, Alexey V.; Grishin, Eugene V.; Rogozhin, Eugene A.
Summary: An interaction of recombinant hairpin‐like cationic peptide EcAMP1 with conidia of plant pathogenic fungus Fusarium solani at the cellular level was studied by a combination of microscopic methods. EcAMP1 is from barnyard grass ( Echinochloa crusgalli L.), and obtained by heterologous expression in Escherichia coli system. As a result, a direct relationship between hyphal growth inhibition and increasing active peptide concentration, time of incubation and fungal physiological condition has been determined. Dynamics of accumulation and redistribution of the peptide studied on fungal cellular cover and inside the conidia cells has been shown. The dynamics are dependent on time of coupling, as well as, a dissimilarity of EcAMP1 binding with cover of fungal conidia and its stepwise accumulation and diffuse localization in the cytoplasm. Correlation between structural disruption of fungal conidia and the presence of morphological changes has also been found. The correlation was found under the influence of peptide high concentrations at concentrations above 32 μM. The results indicate the presence of a binding of EcAMP1 with the surface of fungal conidia, thus, demonstrating a main specificity for its antifungal action at the cellular level. These results, however, cannot exclude the existence of attendant EcAMP1 action based on its intracellular localization on some specific targets. SCANNING 38:591–598, 2016. © 2016 Wiley Periodicals, Inc.